Rodent Control in zero tillage wheat crop fields - Kaur, Navdeep; Singla, Neena (Indian Farming, 2015)
A large amount of crops during pre-harvesting are lost due to damage caused by rodents. Thus, it is very important to control rodent pests in the zero-tillage wheat fields. Management of rodents can be done by various methods as given in this article.